CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI IMPLEMENTASI FIKIH SOSIAL UNTUK PEMBERDAYAAN MASYARAKAT - Yayan Sopyan (Universitas Islam Negeri Jakarta, 2014)
Corporate Social Responsibility (CSR) as an Implementation of Social Fiqh to Empower Society. Corporate Social Responsibility (CSR) is the responsibility of businesses in their undertakings. CSR in the perspective of social fiqh is no only position as an obligation of business that must be there as a part of social life. The government must support business in implementing CSR from voluntary to mandatory requirements so that the existence of CSR can be felt in reality by society. Optimisation of the CSR function in the supporting the success of development can be undertaken by synergising three potentials, namely tertiary education institutions who have the science, sufficient technology and human resources; government who has the space, society and development plans as well as businesses who possess CSR funding.DOI: 10.15408/ajis.v14i1.1253